Postcolonial discourses in Hiligaynon komiks - Jurilla, Jonathan P.; Barrios, John E. (Danyag :the UPV journal of humanities and social sciences, 2002)
"Action/adventure komiks published in Hiligaynon magazine in the 1960s and the 1990s is subjected to a critical reading. The postcolonial approach to literary criticism, especially, Homi Bhaba's concept of 'hybriidy' is used as the analytical tool for this study. The study exposes the 'Worldling and Othering' discourses of Hiligaynon komiks and yet redeems the text by also exposing its subversive side. The hybridity of Hiligaynon komiks allos itself to depict not only the continued insistence of colonial authority but also the refusal of the local to either be totally trapped in the past or be completely contained by the colonial presence."